RINGKASAN KEKUDUSAN MENURUT SURAT 1 PETRUS 1:13-16 DAN IMPLIKASINYA BAGI UMAT KRISTEN MASA KINI - olitos, wahyudi pin (Sekolah Tinggi Teologi Injili Abdi Allah, 2022)
Artikel ini adalah sebuah ringkasan mengenai kekudusan menurut 1 Petrus 1:13-16 dalam hubungan dan penerapannya dengan umat kristen zaman sekarang. Berawal dari rasul Petrus sebagai orang Yahudi yang menganut pemahaman Taurat namun pada akhirnya dipilih oleh Tuhan Yesus sebagai murid, tentu tidak mudah menerima pengalaman penglihatan Illahi tentang kekudusan. Terbukti masih melekat pemahaman kekudusan seperti dalam penjelasan kitab Imamat sehingga tidak mengherankan bila rasul Petrus menolak keras pemberian makanan yang terlarang dalam kitab Imamat sekalipun Tuhan sendiri yang memerintahkan untuk di makan (Kisah Para Rasul 10:11-16). Mengusahakan kekudusan harus tampak bukan untuk membangun citra diri sebagai orang Kristen justru tanggungjawab sebagaimana kewajiban orang Kristen memang sudah seharunya hidup kudus.ABSTRACT This article is a summary of holiness according to 1 Peter 1:13-16 in its relationship and application to Christians today. Starting from the apostle Peter as a Jew who adhered to the understanding of the Torah but in the end was chosen by the Lord Jesus as a disciple, of course it was not easy to accept the experience of God's vision of holiness. It is proven that there is still an understanding of holiness as in the explanation of the book of Leviticus, so it is not surprising that the apostle Peter balked at giving food that was forbidden in the book of Leviticus even though God himself commanded to eat (Acts 10:11-16). Striving for holiness must appear not to build a self-image as a Christian, but rather a responsibility as a Christian's obligation to live a holy life.